ANALISA KEPENTINGAN AKTOR DALAM PEMBERLAKUAN PERATURAN DAERAH NO 10 TAHUN 2006 TENTANG SUMBER DAYA AIR DAN SUMUR RESAPAN - Muhammad Walihuddin; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was conducted to analyze how the interests Analysis Actor In The introduction of Regional Regulation No. 10 of 2006 on Water Resources and Infiltration Wells .. Not optimal penerapam and enforcement of local regulations on water resources and recharge wells in the city of Pekanbaru in particular District of Handsome result in flooding. With the problems that arise in the implementation and enforcement of these regulations in Pekanbaru City, should the actor who has the authority to coordinate the implementation and enforcement of legislation with working units authorized, the Department of Spatial Planning and Building Pekanbaru and Municipal Police Units Pekanbaru city.This study is a descriptive study using a qualitative approach as a tool of analysis. The research was conducted in the city pekanbaru and take samples of data in District Handsome, Pekanbaru. This study uses the documentation and interview with key informants as an information object that aims to achieve the goal to get the information in this study. Data used in this study are primary data and secondary data obtained through documentation and interviews with key informants in this study.Enforcement of a program will be determined by how far the programs will be in demand by the program would threaten certain interests in masyarakat.kelompok community members who feel threatened by the existence of the program will tend to manifest his opposition either openly or terselubung.oleh because it, semakain large presence in disadvantaged groups as a result of the program, the process of the implementation of the policy will be sulit.sebaliknya smaller community groups who feel disadvantaged the easier the program in nimplementasikan.Tidak passes actor in coordinating authority application and enforcement of Regulation area No. 10 of 2006 on Water Resources and Infiltration Wells because many interests that are not in harmony with the other objectives aktirn.There are two things that affect imolementasi policy according to which the contents kebijakandang Grindle policy environment, which also affects the interests of the actors in the enforcement area of water resources and the well resapan.dan -aktor actor must be able to demonstrate efforts to overcome obstacles in the implementation of local regulations to the community and always conduct evaluation of policies that have been done previously as a guide in making improvements forthe future.Keywords: Interest, Policy, Water Resources and Infiltration wells, Regional Regulation.